Comparison of Trap Types, Placement, and Colors for Monitoring Anthonomus musculus (Coleoptera: Curculionidae) Adults in Highbush Blueberries. Issue 2 (28th February 2018) - Silva, Diego; Salamanca, Jordano; Kyryczenko-Roth, Vera; Alborn, Hans T; Rodriguez-Saona, Cesar
Abstract: The cranberry weevil, Anthonomus musculus Say (Coleoptera: Curculionidae), is a key (univoltine) pest of highbush blueberries in the northeast United States. To date, however, no trapping system has been developed to successfully monitor this pest. In 2012–2014, studies were conducted in commercial highbush blueberry farms in New Jersey to 1) evaluate the efficacy of various commercially available traps, designed for other weevil species (e.g., pepper weevil, plum curculio, boll weevil, red palm weevil, and black vine weevil), in capturing A. musculus adults; 2) test whether the relative location of traps within the blueberry canopy affects adult captures and 3) determine the effects of different colored (yellow, white, green, red, blue, brown, and black) sticky traps on weevil captures. For a comparison with existing techniques, we also monitored the number of overwintered adult weevils on blueberry bushes using beat sheet sampling. Of all traps and colors tested, the most A. musculus adults were caught on yellow sticky traps and more adults were captured when these traps were placed at the bottom half of the blueberry canopy, i.e., 0.5–1.0 m above ground. Most weevils were caught on colored traps late in the season (i.e., during bloom), which corresponds mostly to the second (summer) adult generation. Thus, number of overwintered adults caught on traps did not correlate with those on bushes. Although our study identified traps that can be used to capture A. musculus adults, these traps alone (i.e., without semiochemicals) have so far limited applicability for monitoring overwintered adult weevils in highbush blueberries.